Triple Priority: TB/HIV Co-Infection and Treatment Outcomes among Key Populations in The Kyrgyz Republic: A National Cohort Study (2018–2022) - Olga Goncharova; Arpine Abrahamyan; Divya Nair; Mher Beglaryan; Aibek Bekbolotov; Elena Zhdanova; Abdullaat Kadyrov; Rony Zachariah (Tropical Medicine and Infectious Disease, 2023)
Background: Improving tuberculosis (TB) care in key populations is an operational research priority in the Kyrgyz Republic. Here, we describe the characteristics of TB/HIV co-infected individuals, their affiliations with key country-wide population groups, and their TB treatment outcomes. Methods: This was a cohort study using national programmatic data (2018–2022). The key population groups included people with increased exposure to TB, limited access to TB services, and increased risk of acquiring TB. Results: Among 693 individuals with TB/HIV co-infection, the majority (58%) of individuals were from two regions of the Kyrgyz Republic (Chui and Bishkek). Eighty-four percent (84%) individuals had one or more affiliations to eight key population groups, with 49% of the individuals affiliated to ≥2 groups and 92% of the individuals were on both antiretroviral treatment and cotrimoxazole preventive therapy. Overall, 406 (59%) of the individuals had successful outcomes and 287 (41%) of the individuals had unsuccessful outcomes. Unsuccessful outcomes increased from 36% (n-39) with TB/HIV alone to 47% (n-86) with affiliations to ≥3 key population groups (P-0.03). Unsuccessful outcomes were associated with co-morbidities (diabetes mellitus and hepatitis B/C), migration, alcohol use, and extrapulmonary TB. Conclusions: For a long time, people with TB/HIV co-infection have been recognized as a “double priority”. Affiliation to key populations accentuates their status to “triple priority”. We advocate for increased attention and equity towards these populations.